The history of pidgins and creoles against the exceptionalism - Madrid, Rodrigo Lazaresko (2020)
Salikoko S. Mufwene’s conference presents the emergence of pidgins and their relations with creole languages. The speaker describes the traditional approach (which analyses pidgins as ancestor or initial forms of creole languages) aiming to criticize it. Through a historiography-based argumentation, Mufwene introduces the uniformitarian approach, to which pidgins and creoles have no structural peculiarities that justify a differentiation from other languages that emerged from language contact. Moreover, the chronological and geographical diversion in the usage of those two concepts is argued to be an evidence of the unrelatedness of the language types to which they refer. By tracing back the emergence of the pidgins and creole concepts, Mufwene tributes the exclusivism assigned to those languages to the colonialist ideology that prevailed in Europe during the 19th century.